Social Media Metrics For Dummies - Poston, Leslie (London John Wiley, 2012)
Discover how to gauge your online success based on social media metrics with so many social media monitoring and measurement tools available, it can be overwhelming to figure out which tool is right for you when it comes to calculating the success of your social media marketing efforts. This fun and friendly guide helps you determine which tool will serve you best for understanding your online audience. You'll learn to sift through all the information available about social media monitoring and metrics so that you can listen to what is being said about your business, read your analytic dashboard.
Metrics? What the heck is that? -- Navigating the measurement jungle -- Putting your metrics on steroids -- Keeping your finger on the pulse of living, breathing metrics -- Taking the deep dive into advanced metrics -- Predicting future metrics -- The part of tens.
Keywords: Internet marketing; Social media; Marketing research; Online social networks